Antibiotic Resistant Patterns of Salmonella Serovars Isolated from Clinical Stool Samples in Nasarawa State, Nigeria (Lafia Journal of Scientific and Industrial Research, 2025)
Salmonella infections is a major public health concern, resource limited area such as Nasarawa State in Nigeria were the prevalence of drug resistant strains is in the increase. This study was conducted to investigate the prevalence and antibiotic resistance patterns of Salmonella serotypes obtained from clinical stool samples of patients from selected health facilities in Nasarawa State. A cross sectional study design was used in this study. A total of four hundred and fifty (450) stool samples were collected from patients showing symptoms of salmonellosis. Samples collected were cultured on selective media, and the isolates were identified and serotyped using biochemical tests and agglutination reactions respectively. The study identified 18 positive cases, with Salmonella enterica accounting for 94% of infections and S. bongori representing the remaining 6%. Eight distinct serovars were detected, with S. ser. Typhimurium (33%) and S. ser. Enteritidis (22%) being the most prevalent. Other serovars included S. ser. Typhi (11%), S. ser. Heidelberg (11%), S. ser. Agona, S. ser. Paratyphi B, S. ser. Huaian, and S. bongori (6% each). Serovar diversity was higher among male patients, while infection prevalence peaked among individuals aged 41–50 years. Antibiotic susceptibility testing revealed high resistance to Augmentin and erythromycin, while cotrimoxazole, nitrofurantoin, and gentamicin demonstrated efficacy against most isolates. These findings indicate the need for continuous surveillance of Salmonella serotypes and antibiotic resistance patterns to guide treatment and control strategies. This study provides critical epidemiological data for managing Salmonella infections in Nasarawa State and informs public health interventions.
Keywords: salmonella serovars; antibiotic resistance; epidemiology; Nigeria